FAKTOR–FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DAN KINERJA KARYAWAN PT X - KHOIRUNNISA; WASISTO RUSWIDIONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the factors that affect job satisfaction and employee performance. Job satisfaction and employee performance have an important role in the company. The object in this study is PT. X. This form of research uses descriptive research and uses purposive sampling techniques totaling 75 employees. Data was collected through distributing questionnaires using a Likert scale, and analyzed using the SEM-PLS method. The results of this study indicate that the job satisfaction variable has no effect on employee performance, but change management affects job satisfaction and employee performance, organizational commitment affects job satisfaction and employee performance, and leadership style affects job satisfaction and employee performance, it can be concluded that change management, organizational commitment, and leadership style have a significant contribution in influencing job satisfaction and employee performance at PT. X.